2009
DOI: 10.1186/1471-2458-9-451
|View full text |Cite
|
Sign up to set email alerts
|

Over-indebtedness and its association with the prevalence of back pain

Abstract: BackgroundOver-indebtedness is an increasing phenomenon worldwide. Massive financial strain, as found in over-indebted persons, might influence the occurrence of back pain. In this explorative study we examined the prevalence of back pain in over-indebted persons in Germany for the first time ever and compared it to the prevalence of back pain in the German general population.MethodsA cross sectional study comprising 949 participants (52.6% women) was conducted to collect data on the point prevalence of back p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
2
30
0
1
Order By: Relevance
“…Four studies examined the health of those undergoing debt counselling; these are shown in appendix F. Two cohort studies compared over-indebted clients to the general population, finding an increased likelihood being overweight and reporting back pain after controlling for confounds (Munster, Ruger, Ochsmann, Letzel, & Toschke, 2009;Ochsmann, Rueger, Letzel, Drexler, & Muenster, 2009). O"Neill, Sorhaindo, Xiao, and Garman (2005) found that self-rated health was linked to reduced debts after a debt management intervention.…”
Section: Debt Management Clientsmentioning
confidence: 99%
“…Four studies examined the health of those undergoing debt counselling; these are shown in appendix F. Two cohort studies compared over-indebted clients to the general population, finding an increased likelihood being overweight and reporting back pain after controlling for confounds (Munster, Ruger, Ochsmann, Letzel, & Toschke, 2009;Ochsmann, Rueger, Letzel, Drexler, & Muenster, 2009). O"Neill, Sorhaindo, Xiao, and Garman (2005) found that self-rated health was linked to reduced debts after a debt management intervention.…”
Section: Debt Management Clientsmentioning
confidence: 99%
“…The fact that demand for debt counselling exceeds supply by far and the rigorous recruitment criteria of the study (participants had to have attended at least two counselling sessions) meant that study participants were almost certainly over-indebted. Further study design details are published elsewhere [11,14,15]. A test for representativeness conducted among the Rhineland-Palatinate sample reported no differences in sex and age compared to official 2006 statistics of all counselling clients.…”
Section: Methodsmentioning
confidence: 99%
“…Over-indebtedness and financial difficulties are related concepts as they usually affect individuals of lower socio-economic status. Recent studies have found an association with health and health behaviour [8-13], revealing higher prevalences of overweight and obesity [14], back pain [15] and mental disorder [16] in over-indebted individuals in Germany. Research in high-income countries has further suggested an association between financial difficulties and smoking cessation, with those experiencing financial stress being less likely to make quit attempts or successfully quit smoking [17-20].…”
Section: Introductionmentioning
confidence: 99%
“…Low income may affect health through poor material conditions and by hampering social participation and life control (Marmot 2002). In particular, over-indebtedness entails living under strong financial strain, which may be associated with not being able to consume health-enhancing food and services, to meet current health needs, to access health care, and to fully participate in social life (Drentea and Lavrakas 2000;Münster et al 2009;Ochsmann et al 2009). In addition, over-indebtedness is often accompanied with shame, fear of social stigma, anxiety and psychological distress (Hayes 2000;Fitch et al 2007;Drentea and Reynolds 2012;Drentea and Lavrakas 2000), which may have adverse effects on both physical and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, previous studies have demonstrated associations between indebtedness and many types of mental disorders (Alley et al 2011;Bridges and Disney 2010;Cannuscio et al 2012;Drentea and Reynolds 2012;Jenkins et al 2008;McLaughlin et al 2012;Meltzer et al 2013;Nettleton and Burrows 1998;Taylor et al 2007) as well as physical health (Cannuscio et al 2012;Drentea and Lavrakas 2000;Lenton and Mosley 2008;Münster et al 2009;Ochsmann et al 2009). In particular, according to a recent systematic review, over-indebtedness has most consistently been found to be associated with suicidal thoughts, depression, and self-rated health (Turunen and Hiilamo 2014).…”
Section: Introductionmentioning
confidence: 99%